Respon tutur siswa autis terhadap tutur direktif guru dalam interaksi pembelajaran di kelas - Robiah, Siti; Ibrahim, Abdul Syukur; Rofi'uddin, AH. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
The aim of this study is to describe the form, function and response strategies from autistic studentson the teachers’ directive in the classroom. This study used a case study. The results showed that there are two categories of the students’ spoken responses: (1) speech production in the form of assertive, directive, commissive and expressive; and (2) the speech responses are based on the senses including auditory, visual and emotions. In addition, the function of the students’ responses is categorized into two: (i) the effect of speech production in terms of complaining, agreeing, asking, stating something, thanking, apologizing, asserting, reporting, mentioning and offering; and (ii) the students’ responses as the effect of the teachers’ directive speech acts. Furthermore, the students’ response strategies are divided into two categories, namely: (i) internal and external factors, and (ii) the delivery of the students’ responses